Evaluation of Agronomic Performance and Genetic Diversity in Indonesian Pigmented Rice Using SCoT (Start Codon Targeted) Markers - Safitri, Vika Ayu; Fatimah, Fatimah; Wahyu, Yudiwanti; Ardie, Sintho Wahyuning; Mahrup, Mahrup (Bogor Agricultural University, Indonesia, 2026)
Indonesia is rich in biodiversity, including rice (Oryza sativa L.), one of the most important and widely cultivated crops. However, the utilization of local Indonesian rice germplasm in breeding programs remains limited due to the lack of reliable characterization data. Therefore, it’s essential to establish a reliable method to ensure variety protection by breeders. In addition, understanding the relationship between morphological traits and genetic diversity is crucial for a targeted breeding study aimed at evaluating genetic diversity among 12 local rice genotypes from Indonesia through agronomic traits and molecular analysis using start codon targeted (SCoT) markers. Statistical analyses, including cluster and diversity indices, were applied to interpret the data. Characterization was conducted based on the descriptors from The International Rice Research Institute (IRRI) and Bioversity International, while molecular analysis employed 23 selected SCoT primers. The effectiveness of the markers was assessed through polymorphism percentage, PIC values, and cluster analysis. A polymorphism level of 69% was observed, with PIC values ranging from 0.3610 to 0.4646, suggesting that the SCoT markers used provided adequate informativeness for diversity analysis. The study revealed high genetic variability, with heritable traits and informative SCoT markers, demonstrating their potential for pre-breeding and diversity analysis.